2011
DOI: 10.1002/ange.201105970
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Cinchona Alkaloid Thiourea Catalyzed Highly Efficient, Enantioselective Aza‐Henry Reaction of Cyclic Trifluoromethyl Ketimines: Synthesis of Anti‐HIV Drug DPC 083

Abstract: Biologisch interessante chirale Trifluormethyldihydrochinazolinon‐Gerüste werden durch die Titelreaktion mit nur 1 Mol‐% Katalysator in hohen Ausbeuten (bis 97 %) und mit hohen Enantioselektivitäten (bis 98 % ee) aufgebaut. Eine effiziente Synthese des potenziellen Anti‐HIV‐Wirkstoffs DPC 083 nutzte diese hoch enantioselektive Aza‐Henry‐Reaktion als Schlüsselschritt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Among them, catalyst (d, S, S)-Bd exhibited the best catalytic activity and chiral induction ability (entry 8). Solvent screening revealed that THF remains to be the solvent of choice, and other solvents such as chloroform, dichloromethane, toluene, and 1,4-dioxane diminish the yield and/or enantioselectivity (entries [11][12][13][14]. The catalyst loading can be reduced to as low as 1 mol % without a significant decrease in the product yield and enantioselectivity, although a prolonged time was required (entries 15 and 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, catalyst (d, S, S)-Bd exhibited the best catalytic activity and chiral induction ability (entry 8). Solvent screening revealed that THF remains to be the solvent of choice, and other solvents such as chloroform, dichloromethane, toluene, and 1,4-dioxane diminish the yield and/or enantioselectivity (entries [11][12][13][14]. The catalyst loading can be reduced to as low as 1 mol % without a significant decrease in the product yield and enantioselectivity, although a prolonged time was required (entries 15 and 16).…”
mentioning
confidence: 99%
“…The optical rotation data of DPC 083 (10) are entirely consistent with those described in the literature. [13] Thus, the determination of the stereochemistry of 10 was used as the basis for the assignment of absolute configuration reported in Table 1 and Scheme 1.…”
mentioning
confidence: 99%
“…) . Moreover, as already mentioned above, N1‐protected 4‐arylquinazolin‐2(1 H )‐ones are inert in aza‐Henry , Mannich and decarboxylative Mannich reactions. At the same time the investigations on the behavior of 4‐arylsubstituted quinazolin‐2(1 H )‐ones under Strecker reaction conditions showed that upon carrying out this reaction in CH 2 Cl 2 in the presence of 73a (10 mol %) as a catalyst the corresponding adducts were obtained with good yields and moderate ee values.…”
Section: Addition Of Reagents Other Than Hydrogen To Fused Aromatic Pmentioning
confidence: 78%
“…A highly efficient hydrogen bond‐mediated enantioselective addition of nitroalkanes to 4‐trifluoromethylquinazolin‐2(1 H )‐ones 58 (aza‐Henry reaction) has been achieved in toluene at room temperature in the presence of 1 mol% thiourea‐containing quinine derivative as a catalyst (Scheme ). Dihydroquinazolin‐2(1 H )‐ones 59 were obtained in 72–97% yields with good to excellent enantioselectivity (82–98% ee ) unaffected by the electronic nature of the substituents on the aromatic rings of the cyclic ketimine.…”
Section: Addition Of Reagents Other Than Hydrogen To Fused Aromatic Pmentioning
confidence: 99%
“…Dihydroquinazolinones containing at rifluoromethylg roup at the 4-position are known to be biologically active. [8] Literature reports for their asymmetric synthesis are focused on enantioselective additiont o4 -trifluoromethyl-2quinazolinone derivatives, [9][10][11][12][13] and successfully employed nucleophiles include ketone enolates, [9] nitroalkanes, [10] cyanide, [11] indoles, [12] and isocyanoacetates. [13] To the best of our knowledge, there is no report on the catalytic asymmetric arylation of 2-quinazolinone derivatives with arylboron reagents.…”
mentioning
confidence: 99%